Looting: issue of qualification and differentiation in the context of some criminal offenses against property - Ya. H. Lyzohub (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the problem of incorrect understanding of such a relevant today phenomenon as looting, responsibility for which is provided for in Art. 432 of the current Criminal Code of Ukraine. An attempt has been made to show in detail the true content of the objective and subjective features of the legal composition of the considered socially dangerous phenomenon with a simultaneous comparative analysis of it with some criminal offenses against property, which, like looting, involve the taking of property, in particular in the form of theft.